ANALISIS PEMILIHAN SUPPLIER BAHAN BAKU PADA CV GENERAL TIMBER INDONESIA - Supiani, Lilis (Jurnal Manajerial, 2018)
This study aims to determine the system of decision-making and priority criteria in supplier selection. Supplier selection is part of the supply chain. The role of suppliers affect the production process of a company as a supplier is a major business partner in the operation of the company’s work. every manufacturing company has a standard priority suppliers so that it takes an analytical tool for decision-making. Method Analythical Hierarcy Process (AHP) is a decision making method of analysis used in decision-making with a systems approach, where decision-makers are trying to understand a condition of the system and help make predictions in decision-making. Distributing questioner to determine priority criteria CV General Timber supplier in Indonesia. The results of evaluation research in the company’s performance CV General Timber Indonesia, there are five priorities, namely Cost supplier criteria with a weighting of 0.29%, Quality 0,26%, Quantity by 0.16%, Delivery 0.15% and Flexibility of 0.13 %